2013
DOI: 10.1002/ese3.25
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the effects of dwell time duration in a two‐stage injection scheme on exergy terms in an IDI diesel engine by three‐dimensional modeling

Abstract: Dwell duration of multiple-injection scheme is an important parameter, which makes it possible to shift the tradeoff curve between soot and NOx closer to the origin. In this investigation, therefore, energy and exergy analyses are carried out for various two-step injection schemes in which 25% of the total fuel is injected during the second pulse and the dwell time is increased from 5°CA (crank angle) to 30°CA by 5°CA increments. The calculations are performed for a Lister 8.1 indirect injection (IDI) diesel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The ringing intensity parameter is used to distinguish the start of knock phenomenon. Ringing intensity parameter is calculated using Equation (19). This parameter is developed by Eng.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ringing intensity parameter is used to distinguish the start of knock phenomenon. Ringing intensity parameter is calculated using Equation (19). This parameter is developed by Eng.…”
Section: Methodsmentioning
confidence: 99%
“…After solving the governing equations and calculation of the in-cylinder pressure at each time step, the maximum values of pressure rise rate, in-cylinder pressure, and temperature are selected and the ringing intensity is calculated using Equation (19). The higher values of ringing intensity indicate a higher likelihood of diesel knock.…”
Section: Ri = 1 2γmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Exergy concept is applied in several studies to investigate the performance of the systems and cycles. 4650 Although exergy cannot be saved during a process, it is partially or totally lost due to irreversibility in the systems. In this regard, the contribution of all components and their contribution to the total exergy destruction through the system can be separately analyzed and calculated.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Moreover, it was indicated that combustion timing has to be adjusted just before the sharp increase in unburned species losses. Jafarmadar and Zehni carried out exergy analysis in combustion chamber of the IDI diesel engine by three‐dimentional modeling. They investigated dwell time duration effect on exergy terms, which resulted in work exergy and exergy efficiency decrease when dwell time increased from 5 ° to 30 °CA.…”
Section: Introductionmentioning
confidence: 99%